UPAYA KPPU DALAM MENCEGAH PRAKTIK KARTEL DAGING AYAM BROILER - Dionesius, Daud; Hadi, Hernawan (Jurnal Privat Law, 2019)
AbstractThis article describes the suggestion and also efforts made by KPPU in preventing the occurrence of cartel poultry practice in Indonesia. The duties and authorities of KPPU in preventing and avoiding monopolistic practices and unfair business competition conducted by business actors is by giving advice to the government (case study of cartel practice of broiler chicken in Indonesia). This article uses normative legal research methods with prescriptive research properties. The research approach uses legal approach and legal source using primary legal material where the main legal material comes from legislation, secondary law material obtained from legal literature materials, as well as non-legal legal materials that have relevance to the research topic. Based on the research of the Law of the Republic of Indonesia Number 5 Year 1999 concerning Prohibition of Monopolistic Practices (Law No. 5/1999) and Unfair Business Competition was formed to overcome Unhealthy Competition among business actors, one of the Cartel. Indonesia’s poultry industry is due to the impact of cartel allegations that occurred in2015 by some manufacturers. This is done by doing an early rejection of 2 million parent stock, so that broiler chickens circulating in society / consumers to be limited. As a result, the price of broiler chicken meat in the market can rise due to the decrease in the number of offer from the producers. In order to prove the violation and Article 11 (cartel) of Law Number 5 Year 1999, Article 11 requires fulfillment of the agreement element. Nevertheless it has become the duty and authority of KPPU in giving advice to the government and efforts in order to prevent cartel practices especially in the field of poultry happen again. So writer interested to discuss about suggestion and effort of KPPU in preventing poultry cartel.Keywords: Cartel; KPPU; Broiler ChickenAbstrakArtikel ini menjabarkan tentang saran dan juga upaya yang dilakukan KPPU dalam mencegah terjadinya praktik kartel perunggasan di indonesia. Tugas dan kewenangan KPPU dalam mencegah dan menghindari praktik monopoli dan persaingan usaha tidak sehat yang dilakukan oleh para pelaku usaha adalah dengan memberikan saran kepada pemerintah (studi kasus praktik kartel daging ayam broiler di indonesia). Artikel ini menggunakan metode penelitian hukum normatif dengan sifat penelitian preskriptif. Pendekatan penelitian menggunakan pendekatan undang-undang dan sumber hukum menggunakan bahan hukum primer dimana bahan hukum utama berasal dari perundang-undangan, bahan hukum sekunder yang diperoleh dari bahan kepustakaan hukum, serta bahan hukum non-hukum yang mempunyai relevansi dengan topik penelitian. Berdasarkan hasil penelitian Undang-Undang Republik Indonesia Nomor 5 Tahun 1999 Tentang Larangan Praktek Monopoli (UU No 5/1999) dan Persaingan Usaha Tidak Sehat dibentuk untuk mengatasi Persaingan tidak sehat diantara pelaku usaha, salahsatunya Kartel. Industri perunggasan Indonesia tekena dampak dari dugaan kartel yang terjadi pada tahun 2015 oleh beberapa produsen . Hal ini dilakukan dengan cara melakukan afkir dini terhadap 2 juta parent stock, sehingga ayam broiler yang beredar di masyarakat/konsumen menjadi terbatas. Mengakibatkan, harga daging ayam broiler di pasaran bisa naik karena berkurangnya jumlah peawaran dari produsen. Dalam rangka membuktikan terjadinya pelanggaran dan Pasal 11 (kartel) Undnag- Undang Nomor 5 Tahun 1999, pasal 11 mensyaratkan pemenuhan unsur perjanjian. Namun demikian sudah menjadi tugas dan kewenangan KPPU dalam memberikan saran kepada pemerintah serta upaya dalam rangka mencegah praktik kartel khususnya dibidang perunggasan terjadi kembali. Maka penulis tertarik untuk membahas mengenaisaran serta upaya KPPU dalam mencegah kartel unggas.Kata kunci : Kartel; KPPU; Daging Ayam Broiler